Age patterns of under-five mortality in sub-Saharan Africa during 1990-2018: a comparison of estimates from demographic surveillance with full birth histories and the historic record - Eilerts,H; Prieto,JR; Eaton,J; Reniers,G (Demographic Research, 2021)
BACKGROUND: In Sub-Saharan African countries which often lack high-quality vital registration data, estimates of under-five mortality (U5M) rely heavily on full birth histories (FBHs) collected in surveys and model age patterns of mortality calibrated against vital statistics from other populations. Health and Demographic Surveillance Systems (HDSS) are al-ternate sources of population-based data in much of sub-Saharan Africa, which are less formally utilized in estimation. OBJECTIVE: The objective of this study is to compare the age pattern of U5M in African HDSS with FBHs from the Demographic and Health Surveys (DHS) and Multiple Indicator Cluster Surveys (MICS), the Human Mortality Database (HMD), and model age patterns.METHODS: We examined the relative levels of neonatal, post neonatal, infant, and child mortality across data sources. We directly compared estimates for DHS and MICS subnational regions with HDSS, and used OLS regression to identify data attributes that correlated with the disparity between estimates. RESULTSH: DSS and FBH data suggests that African populations have higher levels of child mortality and lower infant mortality than the historic record. This age pattern is most explicit for Western African populations, but also characterizes data for other sub regions. The comparison between HDSS and FBH suggests that FBH child mortality is biased downward. The comparison is less conclusive for neonatal and infant mortality. CONTRIBUTION: This study questions the practice of using model age patterns derived from largely high-income settings for inferring or correcting U5M estimates for African populations. It also highlights the considerable uncertainty around the consistency of HDSS and FBH estimates of U5M.